Adding sauna bathing after endurance training: a practical insight from the word's top junior tennis player - Novak, D.; Barbaros Tudor, P.; Matkovic, B. R. (Acta Kinesiologica, 2018)
Sauna bathing is a form of heat exposure characterized by a short-term exposure to high air temperatures. There is very little evidence of the effects of sauna bathing on athletes. This case study involved the world`s top junior female tennis player and 3 weeks of post-training sauna bathing was performed. Sauna bathing was performed immediately after endurance training sessions (12 bathing sessions spread over 3 weeks) by including the run to the sauna facility as a part of her training. Aerobic capacity, speed, agility, lower-body power and blood parameters were measured. All measurements were performed the day before the preparations training period and the day after completion of the preparation period. After the period of 3 weeks run time to exhaustion increased by 9.67% (15.5 vs. 17 min), maximal relative oxygen uptake by 8.58% (46.23 vs. 50.20 ml/kg/min) and anaerobic threshold by 16.66% (12 vs. 14). Plasma volume and red cell count increased by 7.47% (3.48 vs. 3.74 L) and 7.12% (3.93 vs. 4.21 10^12/L)respectively. Small progress occurred in motor abilities, agility and lower body power. We concluded that 3 weeks of post-exercise sauna resulted in no adverse effects on performance and the possible positive impact was present. More research is needed toconfirm these findings in larger sample